Strategi Pemasaran Museum Topeng Cirebon dalam Meningkatkan Jumlah Kunjungan Wisatawan - Fikri Firdaus; hafni khairunnisa; Haulah Nakhwatunnisa (UIN Mahmud Yunus Batusangkar, 2026)
This research aims to analyze the marketing strategy implemented by the Cirebon Mask Museum and to formulate alternative strategies to increase the number of tourist visits. Despite having unique collections and high philosophical value, the Cirebon Mask Museum still faces challenges in terms of visibility and the dominance of a single visitor segment. This study employs a qualitative approach with the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method. Data were collected through in-depth interviews, field observations, and documenThis research aims to analyze the marketing strategy implemented by the Cirebon Mask Museum and to formulate alternative strategies to increase the number of tourist visits. Despite having unique collections and high philosophical value, the Cirebon Mask Museum still faces challenges in terms of visibility and the dominance of a single visitor segment. This study employs a qualitative approach with the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method. Data were collected through in-depth interviews, field observations, and documentation studies. The results show that the strategic position of the Cirebon Mask Museum is in Quadrant I (Aggressive Strategy) with coordinate values of (+2.01; +1.84). This indicates that the museum possesses significant internal strengths to maximize external opportunities. The primary recommended strategy is the S-O (Strengths-Opportunities) strategy, which includes optimizing digital campaigns based on the collections’ philosophical narratives, developing collaborative tourism packages with the tourism industry, and enhancing educational programs to expand market reach beyond the student segment. Improvements in physical accessibility and the diversification of social media content are key to increasing market penetration for general and international touriststation studies. The results show that the strategic position of the Cirebon Mask Museum is in Quadrant I (Aggressive Strategy) with coordinate values of (+2.01; +1.84). This indicates that the museum possesses significant internal strengths to maximize external opportunities. The primary recommended strategy is the S-O (Strengths-Opportunities) strategy, which includes optimizing digital campaigns based on the collections’ philosophical narratives, developing collaborative tourism packages with the tourism industry, and enhancing educational programs to expand market reach beyond the student segment. Improvements in physical accessibility and the diversification of social media content are key to increasing market penetration for general and international tourists